Method for treating autosomal recessive BESTROPHIN disease and evaluation method of autosomal recessive BESTROPHIN disease - JACOBSON STUART G; AGUIRRE, GEORGE, D; GUZIEWICZ KEITH E; SIDDECIYAN ARTO V; BELTRAN WILLIAM A (2022)
Provided herein are methods of treating bestrophin disease, and methods of treating bestrophin disease. The methods comprise administering to an eye of a subject a dose of a recombinant adeno-associated virus (rAAV) vector comprising a nucleic acid sequence encoding a human BEST1 protein, wherein the subject has two mutated BEST1 alleles. Methods of assessing treatment of retinal degeneration are also provided. 本文提供了治疗bestrophin病的方法。所述方法包括向受试者的眼睛施用一定剂量的包含编码人BEST1蛋白的核酸序列的重组腺相关病毒(rAAV)载体，其中所述受试者具有两个突变的BEST1等位基因。还提供了评估视网膜变性治疗的方法。